Pembangunan pelancongan dan impaknya terhadap persekitaran fizikal pinggir pantai - Jamaluddin Md. Jahi, (Environmental Management Society, Malaysia, 2009)
The tourism industry in this country has developed tremendously since about three decades ago. The tourism development, especially during the initial stage has made the coastal zone as the main attraction of the country’s tourism industry. Presently, even though several other tourism destinations have been developed, the coastal areas are still attracting not only foreign tourists, but also domestic tourists. In line with the achievement of tourism industry and its importance to generating income to the local population, tourism operators and the nation as a whole, its negative impact on the coastal zone is also on the rise. This is because the coastal zone is not only very dynamic, but also fragile. As such, the number of visitors to tourism destination, their activities and the duration of use if exceeded its optimum limit may deteriorate the tourism destination. Negative impacts on the physical environment such as the loss of habitat, problem of pollution, erosion, and sedimentation are not easily observable, let alone to be given an economic value within a short time. Nevertheless, human activities in the coastal zone not only have disturbed, but also intensified coastal physical processes. Infact, the activity of developing a tourism destination causes the loss of natural habitat. After the destination has been in operation with various activities it can cause coastal erosion problem, sedimentation and pollution that may lead to the destination being ‘abandoned’ by tourists. Sinvce tourism industry is a major contributor to the national income, it is suggested that an integrated coastal zone management system be created in order to have sustainable tourism development